The effects of genre on the syntactic complexity of argumentative and expository writing by Chinese EFL learners - Pu, Liping; Heng, Renquan; Cao, Cong (Frontiers in Psychology, 2022)
Genre-based research concerning syntactic complexity and its influence on the teaching and assessing of EFL writing has attracted much attention from both researchers and teachers in the field of second language acquisition. However, the vast majority of studies have either focused on one single genre or made comparisons between narrative and non-narrative writing (mostly argumentative) in academic contexts without examining how EFL writers perform across non-narrative genres. Also, the measures used in quantifying the syntactic complexity of writing are varied, thus leading to inconsistent findings. This study examined the effects of genre on syntactic complexity of writing by comparing argumentative and expository compositions written by Chinese EFL learners over one academic year. Participants were asked to write eight compositions (with two genres alternated), four argumentative and four expository. The compositions were parsed via Syntactic Complexity Analyzer, a computational system automatically operating with 14 measures of syntactic complexity tested in second language writing development studies. The results with time as within-subjects variable showed a significant development of syntactic complexity in both argumentative and expository compositions over the year. Meanwhile, the paired-sample t-test with genre as within-subjects variable demonstrated a higher syntactic complexity in argumentative compositions than in expository ones in most of the 14 measures examined at four time points over the year. Also, a two-way repeated measures analysis of variance is conducted with genre and time as independent variables, testifying to an interactional effect of time and genre on some of the 14 measures. The findings concluded in this study test and verify the impact genre exerts on syntactic complexity of writing, thus providing implications for both teachers and researchers to be more informed in teaching and assessing EFL writing, and for students to be more conscious of genre difference in EFL writing.